Assessing the Readiness of Mathematics Teachers, Students, and Parents for Modular Distance Learning - Estoconing, Friendian; Maca, Cherry Mae; Abuyabor, Maribel (Journal of Interdisciplinary Perspectives, 2025)
This study investigated the level of readiness of mathematics teachers, students, and parents in modular distance education. A total of 10 teachers, 428 students, and 428 parents participated in the study. Using a descriptive-correlational research design, the findings revealed that teachers and parents exhibited the lowest levels of attitude toward modular distance education. Additionally, a significant relationship was found between students’ age and their ability to learn independently, indicating that older students tend to be more self-sufficient than younger ones. Teachers demonstrated readiness in monitoring students' outputs, providing feedback, and offering tutorials based on students’ performance. Students were prepared regarding time management, commitment, independent learning, and attitude toward modular distance education. Parents showed readiness to manage their time and support their children's educational needs. Overall, among the three groups, teachers had the highest level of readiness, followed by students and parents. Based on these findings, enhancement training should address areas with the lowest levels of readiness, aiming to improve further the preparedness of mathematics teachers, students, and parents for modular distance education.